2012
DOI: 10.1002/jcb.24030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physiological importance of metallothionein protein expressed by Tetrahymena cadmium metallothionein 1 (TMCd1) gene in Escherichia coli

Abstract: TMCd1 is a cadmium inducible metallothionein (MT) gene. In the present study the TMCd1 gene of a ciliate protozoan has been expressed in E. coli and the function of the expressed TMCd1 protein as a metal-binding protein has been evaluated. The growth of E. coli cells expressing the GST fused TMCd1 proteins in the presence of cadmium metal clearly demonstrated the role of TMCd1 as a metal-binding protein. The metal accumulation experiments showed that the bacterial cells expressing the functional TMCd1 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…MTs are more stable and less prone to proteolytic cleavage in metal bound state as compared to unbound state. The stable expression of MT protein was achieved when the cadmium was added to the cell cultures . Bioaccumulation experiments revealed that the E. coli cells expressing the TMCd1 protein accumulates cadmium at 7.9 μM/mg of cell wet weight .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTs are more stable and less prone to proteolytic cleavage in metal bound state as compared to unbound state. The stable expression of MT protein was achieved when the cadmium was added to the cell cultures . Bioaccumulation experiments revealed that the E. coli cells expressing the TMCd1 protein accumulates cadmium at 7.9 μM/mg of cell wet weight .…”
Section: Discussionmentioning
confidence: 99%
“…The stable expression of MT protein was achieved when the cadmium was added to the cell cultures . Bioaccumulation experiments revealed that the E. coli cells expressing the TMCd1 protein accumulates cadmium at 7.9 μM/mg of cell wet weight . The induced E. coli /pET‐TMCd1 cells accumulated Cd 2+ at a 19‐fold higher amount than that of the control cells lacking the TMCd1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis resulted in expression of a full length protein which is useful to characterize the protein and analyze its metal binding capacity. Suleman and Shakoori [] have also reported the functional analysis of a full length expressed mutated cadmium MT.…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis resulted in expression of a full length protein which is useful to characterize the protein and analyze its metal binding capacity. Suleman and Shakoori [2012] have also reported the functional analysis of a full length expressed mutated cadmium MT. EXPRESSION AND PURIFICATION OF TfCuMT E. coli BL21C þ host cells were transformed with mutated gene cloned in pET21a expression vector for expression purpose.…”
Section: Mutagenesis Of Tfcumtmentioning
confidence: 99%
“…Some studies reported that the prokaryotic expression could be applied to researching the eukaryotic gene functions (Evans et al . ; Suleman and Shakoori ). To further elucidate the relationship between AtLCD and AtDCD genes and tolerance to heavy metal, we cloned these two genes.…”
Section: Introductionmentioning
confidence: 98%